Феномен злочину в романі А. Ю. Заріна «Казнь» - Перцева, Вікторія; Pertseva, Victoria (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено творчість російського письменника кінця XIX – початку ХХ ст. Андрія Юхимовича Заріна. Мета роботи – аналіз роману А. Ю. Заріна «Казнь» із точки зору авторського розуміння феномену злочину. Зокрема, проаналізовано художні особливості його перших кримінальних нарисів, а також інтерпретацію теми злочину в цьому романі. The article is devoted to the activity of Russian writer Andrei Efimovich Zarin who lived in the late XIX – early XX century. The aim of the work is to analyze the novel by A. E. Zarin «Execution» from the point of the author’s understanding the phenomenon of the crime. In particular, the artistic features of his first crime essays and the theme of the crime interpretation in the given novel are analyzed. The urgency of this theme is conditioned by the fact that literary activity of Zarin, as one of the representatives of Russian detective school, hasn’t been the topic of serious research of specialists in literature studies. The analysis of the novel «Execution» permits to state that a general problem of guilt which had been raised by A. E. Zarin is underlined by the crime that the writer used as a key to expose the inner world of his heroes. In particular, psychological and moral split personality and revenge made the hero, who is a quite sensible person, to act against logical decisions and common sense and his emotional sufferings discover his unpredictable qualities. Depicting the search of the murderer, Zarin extends crime understanding and, in such a way, at the example of this single case he underlines the common atmosphere in Russian province which is saturated with crimes. According to the writer’s opinion, the phenomenon of the crime lies in the fact that it is a sort of totality of objective and subjective characteristics and the criminal is a victim and an executioner at the same time.
The Phenomenon of a Crime in A. E. Zarin’s Novel «Execution»
Keywords: кримінальна белетристика; феномен злочину; літературна кримінографія; принцип таліона; підтекст; criminal fiction; crime phenomenon; literary criminography; the principle of retaliation; subtext